Cervical length measurement: Comparison of transabdominal and transvaginal approach. Issue 1 (February 2015) - Westerway, Susan Campbell; Pedersen, Lars Henning; Hyett, Jon
Abstract: Objective : To compare transabdominal (TA) and transvaginal (TV) ultrasound assessment of cervical length at 16–41 weeks gestation. Methods : TA and TV ultrasound measurements of cervical length were made on 491 pregnancies of 16–41 weeks gestation. Cervical length was measured from internal to external cervical os. Bland‐Altman plots and Wilcoxon signed rank test were used to evaluate differences between TA and TV measurements. Results : The validity of the TA method depended on cervical length. Although the TA method underestimated cervical length by 2.0 mm on average ( P < 0.001), Bland Altman plots showed an inverse trend with shorter cervixes. In women with a cervix < 25 mm (n = 30) based on TV scan measurement, TA overestimated cervical length by 12 mm (P < 0.001). The sensitivity and specificity of TA as a test to detect cervical length < 25 mm were 10% (95% CI: 2.1–26%) and 94% (95% CI: 92–96%) respectively; the negative LR was 0.96 (95% CI: 0.84–1.08). The maximum area under the ROC curve would be obtained at a TA cut‐off = 32 mm (to detect a cervix < 25 mm), corresponding to a sensitivity of 77% and a specificity of 58%. Conclusion : TA measurements do not reflect TV assessment accurately, particularly if the cervix is short. At 24–34 weeks, a policy of proceeding to TV scan if TA measurement is < 25 mm will only detect 10% of affected pregnancies and has a poor positive predictive value so is of limited value as a predictive tool for women attending with symptoms and signs of preterm labour > 24 weeks gestation. There is no value in TA assessment of the cervix > 36 weeks.